Analysis of Forehand and Backhand Stroke Accuracy and Lateral Epicondylitis Pain among Recreational Tennis Players - Mathew A, Ashish; Farzana, S F Mariyam; T N, Suresh; M, Arvind; V, Prithiha (Malikussaleh University, Aceh, Indonesia, 2025)
The tennis matches require short explosive bursts of energy per match or practice session, and an average tennis match lasts less than one hour or as long as five hours. Tennis players most prominently use the primary ground strokes, such as forehand and backhand strokes. The forehand and backhand strokes are simultaneously activated by a complex sequence of muscle activity that incorporates smooth trunk and lower extremities coordination patterns. Accuracy of the forehand and backhand stroke plays a dominant role in the tennis matches, because accurate movement leads to high-performance skills. The contraption of this study promotes the knowledge on the influence of lateral elbow pain, which affects the players' accuracy in performing the ground strokes during a match, significantly decreasing the players' performance. The participants were recruited according to the inclusion and exclusion criteria. The participants' lateral epicondylitis was assessed using the Cozens test, pain was evaluated using the Numeric pain rating scale, and the ground stroke accuracy was assessed using the Wiebe tennis performance test. During the forehand stroke, the participants reported a visual analogue scale with a mean value of 2.46 and an accuracy rate of 65.71. During the backhand stroke, the participants reported a visual analogue scale with a mean value of 5.66 and an accuracy rate of 37.93. This study concludes that the pain score significantly increased in double and single backhanded strokes, with a decreased accuracy rate. This study also concludes that at least a positive correlation exists between pain intensity and the accuracy rate in the backhand stroke.